1974
DOI: 10.1042/bj1390661
|View full text |Cite
|
Sign up to set email alerts
|

The use of deoxyfluoro-d-galactopyranoses in a study of yeast galactokinase specificity

Abstract: 1. 2-Deoxy-2-fluoro-d-galactose, 3-deoxy-3-fluoro-d-galactose, 4-deoxy-4-fluoro-d-galactose, 6-deoxy-6-fluoro-d-galactose and 2-deoxy-d-lyxo-hexose are substrates for yeast galactokinase. 2. The variation in K(m) values for the d-hexose derivatives was not associated with a variation in the value of K(m) for MgATP(2-) indicating that the binding of MgATP(2-) is not modified by the binding of the sugar substrate. 3. Donated H bonds from OH-3, OH-4 and OH-6 and an accepted H bond to OH-2 of the d-hexose are impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…2): the glycogen phosphorylases (16), which convert glycogen (9) into D-glucose-1-phosphate (10); fucokinases, which transfer a phosphate from ATP to the anomeric position of L-fucose (12) to provide ␤-L-fucose-1-phosphate (13) (17); and the galactokinases (GalK), which catalyze the formation of ␣-D-galactose-1-phosphate (Gal-1-P, 15) from D-galactose (14) and ATP. Previous studies have revealed that GalK from various sources have a limited substrate scope (18)(19)(20)(21), and in all C-1 kinases studied thus far, a strict adherence to either D-sugars (GalK and glycogen phosphorylases) or L-sugars (as in fucokinase) was observed. Thus, to apply any of these kinases for generating a randomized sugar phosphate library, their monosaccharide substrate promiscuity must first be enhanced.…”
mentioning
confidence: 99%
“…2): the glycogen phosphorylases (16), which convert glycogen (9) into D-glucose-1-phosphate (10); fucokinases, which transfer a phosphate from ATP to the anomeric position of L-fucose (12) to provide ␤-L-fucose-1-phosphate (13) (17); and the galactokinases (GalK), which catalyze the formation of ␣-D-galactose-1-phosphate (Gal-1-P, 15) from D-galactose (14) and ATP. Previous studies have revealed that GalK from various sources have a limited substrate scope (18)(19)(20)(21), and in all C-1 kinases studied thus far, a strict adherence to either D-sugars (GalK and glycogen phosphorylases) or L-sugars (as in fucokinase) was observed. Thus, to apply any of these kinases for generating a randomized sugar phosphate library, their monosaccharide substrate promiscuity must first be enhanced.…”
mentioning
confidence: 99%
“…Figure 2 illustrates the substrate profiles of wild‐type L. lactis GalK and the L. lactis Y385H GalK mutant. The L. lactis wild‐type enzyme accepted 13 sugar substrates, a striking expansion of the typically limited substrate scopes observed for the GalK family 2427. Among these new monosaccharide substrates were three notable C‐4‐substituted sugars ( 12 , 13 , and 14 ) and two unique L ‐configured sugars ( L ‐altrose, 22 , and L ‐glucose, 23 ), all of which failed as active substrates for native GalKs from other sources 2427.…”
Section: Representative Activities and Product Mass For Each Enzymatmentioning
confidence: 96%
“…The L. lactis wild‐type enzyme accepted 13 sugar substrates, a striking expansion of the typically limited substrate scopes observed for the GalK family 2427. Among these new monosaccharide substrates were three notable C‐4‐substituted sugars ( 12 , 13 , and 14 ) and two unique L ‐configured sugars ( L ‐altrose, 22 , and L ‐glucose, 23 ), all of which failed as active substrates for native GalKs from other sources 2427. As expected, the L. lactis Y385H mutant was even more promiscuous with several new structures (Figure 2, 2‐deoxy‐ D ‐glucose, 15 , 6‐amino‐6‐deoxy‐ D ‐galactose, 17 , and 6‐azido‐6‐deoxy‐ D ‐galactose, 19 ) also weakly recognized by this variant.…”
Section: Representative Activities and Product Mass For Each Enzymatmentioning
confidence: 96%
“…25 In this study, they demonstrated the conversion of 6FGal to 6FGal-1P using a yeast-derived galactokinase (GalK) in the presence of ATP. Westwood et al 26 later evidenced that 2FGal, 3FGal and 4FGal could be converted by the same enzyme to 2FGal-1P, 3FGal-1P and 4FGal-1P respectively. The results of their kinetic study suggests the yeast-derived GalK has lower affinity for the four fluorinated substrates when compared with the natural Gal substrate (in the order Gal > 2FGal > 3FGal ≈ 6FGal << 4FGal).…”
Section: Fluorinated Galactose-1-phosphate and Udp-galactose Donorsmentioning
confidence: 99%